2017
DOI: 10.1111/jpn.12830
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of inulin and soya bean oligosaccharide on skatole production and the intestinal microbiota in broilers

Abstract: The experiment was conducted to investigate the in vitro effects of inulin and soya bean oligosaccharide (SBO) on the metabolism of L-tryptophan (L-try) to skatole production, and the intestinal microbiota in broilers. Treatments were as follows: caecal microbiota control (Cc), Cc + inulin, Cc + SBO, rectal microbiota control (Rc), Rc + inulin and Rc + SBO. Microbial suspensions were anaerobically incubated at 38°C for 24 hr. The results showed that concentrations of skatole and acetic acid were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 47 publications
3
30
1
Order By: Relevance
“…The present study showed that the greater the total bacterial population, the higher the production of skatole and VFAs, which agrees with the findings of Li et al (2009) and Liu et al (2018).…”
Section: The Correlation Between Intestinal Skatole Production and supporting
confidence: 92%
See 3 more Smart Citations
“…The present study showed that the greater the total bacterial population, the higher the production of skatole and VFAs, which agrees with the findings of Li et al (2009) and Liu et al (2018).…”
Section: The Correlation Between Intestinal Skatole Production and supporting
confidence: 92%
“…Similar to Yang et al (2017) and Liu, Hou, Yang, Zhao, and Dong (2018), the findings of the present study indicate that both propionate and butyrate were undetected in most of the intestinal digesta samples. It was reported that the species or culture conditions of intestinal bacteria largely influenced the type and content of VFAs, and in conditions of excessive carbon sources, Bifidobacteria mainly produce acetate and lactate (Chen, Cao, & Liu, 2006;Wolin et al, 1999).…”
Section: Vfa and Lactate Levels In Different Intestinal Segments Ofsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar study in mice revealed that administration of SBO improved the numbers of bene cal intestinal microbes [16]. In vitro studies have revealed that SBO can improve the gut microbiota balance in colon and modulate its metabolism in pigs [7], changed in the intestinal microbiota and reduced the production of odor compounds in broilers [17,18]. Antibiotics work primarily by reshaping the intestinal microbiota [19], which is known as a unique ecosystem to play a crucial role in host health and metabolism [20][21][22].…”
Section: Introductionmentioning
confidence: 95%